Challenges in universal coverage and utilization of insecticide-treated bed nets in migrant plantation workers in Myanmar - Nyunt, Myat H (BioMed Central, 2014)
BACKGROUND: High coverage of the bed nets can reduce mortality and morbidity of mosquito-borne diseases including malaria. Although the migrant workers are at high risk of malaria, there are many hidden challenges in universal coverage and utilization of the insecticide-treated nets (ITNs) in this populations. METHODS: Cross sectional study was conducted in 170 migrant workers in palm oil plantation sites in Tanintharyi Region and 175 in rubber plantation sites in Mon State. A multistage stratified cluster sampling was applied to select the participants. During household visit, face-to-face interviews using structured pre-coded, pre tested questionnaires and direct observation on installation of the bed nets was conducted. Two focus group discussions in each site were done by sample stratified purposive sampling method mainly focused on effective utilization of bed nets. RESULTS: Among them, 332 (96.2%) had a bed net and 284 (82.3%) had an ITN, while 204 (59.1%) had unused extranets. Among the ITNs users, 28.9% reported problems including insecticide smell (56.9%), dizziness (20.2%), headache (12.8%) and itchiness (9.2%). More than 75% received ITNs from health authorities and NGOs free-of-charge. More than 70% wanted to buy a net but they were unaffordable for 64% of them. On observation, only five families could show no bed net, but 80% showed 1–3 ITNs. Consistent utilization in all seasons was noted in 189 (53.1%), that was higher in palm oil plantation than rubber plantation workers (p = 0.0001) due to the nature of the work at night. Perceived malaria risk was also significantly higher ITNs consistent users than non-users (p = 0.0004) and better willingness to buy an ITN by themselves (p = 0.0005). They said that effectiveness of the ITNs was reduced after 6 months and 2–3 times washing. They wished to receive more durable smooth nets with small holes in lace. Misuses of the ITNs such as use the nets for animals and fishing, were also noted. CONCLUSION: There should be efforts to improve effective utilization of ITNs by continuous mass free distribution, durability monitoring, surveillance of insecticide resistance of the vector and behaviour change interventions in migrant plantation workers.